2010
DOI: 10.1039/c001344g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical switching behaviour of tricarbonylrhenium(i) complexes of a new redox active ‘Pincer’ ligand

Abstract: The structures and optoelectronic properties of tricarbonylrhenium(I) complexes of di(2-pyrazolyl-p-tolyl)amine in its neutral and deprotonated (uninegative amido) form were investigated. Reactions of the complexes with Brønsted acids or bases result in distinctive changes of colour and electrochemical activity owing to the non-innocent nature of the ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 17 publications
3
35
0
Order By: Relevance
“…The shape and energies of these pi-radical bands are nearly identical to those found in the rhenium(I) or rhodium(III) complexes of this oxidized ligand. 24,25 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The shape and energies of these pi-radical bands are nearly identical to those found in the rhenium(I) or rhodium(III) complexes of this oxidized ligand. 24,25 …”
Section: Resultsmentioning
confidence: 99%
“…The coordination chemistry of tricarbonylrhenium(I) 24 and rhodium 25 complexes showed that these pincer-type ligands are electrochemically active and chemically non-innocent. The electronic properties and reactivity of the complexes could be predictably fine-tuned by substituting at the pyrazolyl, at the para -aryl positions, or even at the metal center.…”
Section: Introductionmentioning
confidence: 99%
“…Since multiple states characterize redox-active groups, future applications in magnetism (bistable switching) can be envisioned, [68] as can applications as ATRP catalysts, where redox potentials are of central importance.…”
Section: Discussionmentioning
confidence: 99%
“…[185][186][187][188] It was also observed that the chloride of one complex bonds to the adjacent complex through the acidic methylene CH (Cl/H ¼ 2.638(2)Å, Cl/C ¼ 3.569(7)Å), leading to the formation of a single-stranded linear polymer. A face-to-face p-stacking interaction (centroid-centroid distance of 3.736Å) occurs between the phenyl group and 1,2,3-triazole units on adjacent complexes to produce the double-stranded structure.…”
Section: 95mentioning
confidence: 99%